Characterization of Drosophila Telomeric Retroelement TAHRE: Transcription, Transpositions, and RNAi-based Regulation of Expression. - Shpiz, S.; Kwon, D.; Uneva, A.; Kim, M.; Klenov, M.; Rozovsky, Y.; Georgiev, P.; Savitsky, M.; Kalmykova, A. (Molecular Biology and Evolution, 2007)
Telomeres in Drosophila are maintained by transpositions of specialized telomeric retroelements HeT-A and TART rather than by the telomerase activity adding short DNA repeats to chromosome ends in other eukaryotes. A novel element TAHRE was previously found in the telomeric regions of the genome of Drosophila melanogaster stock sequenced by the Genome Project. Comparative genomic analysis confirmed by Southern analysis and in situ hybridization of polytene chromosomes reveals conserved TAHRE elements in the genomes of melanogaster subgroup species. Spontaneous attachment of TAHRE retroelement to the broken end of terminally deleted chromosome allows us to consider TAHRE as the third retrotransposon family involved in telomere maintenance in Drosophila. The abundance of TAHRE transcripts in ovaries is strongly upregulated owing to mutations in the RNA interference genes spn-E, aub, piwi, and vasa locus. spn-E mutations eliminate TAHRE-specific short RNAs in the ovaries. These data suggest that TAHRE is a conservative element involved along with HeT-A and TART in telomere maintenance and a target of the RNAi-based system in the Drosophila germ line. This study reveals similar distribution of TAHRE and HeT-A transcripts, which accumulate in the oocyte, whereas TART transcripts localize in nurse cells. Taking into account a common pattern of HeT-A and TAHRE expression, one may consider TAHRE as a source of reverse transcriptase enzymatic activity for HeT-A transpositions in ovaries.